Early intervention of crossbite by planas direct tracks: Follow up report after seven years - Garbin, Artênio José Isper [UNESP]; Wakayama, Bruno [UNESP]; Saliba, Tânia Adas [UNESP]; Garbin, Cléa Adas Saliba [UNESP] (Colegio Mayor de Nuestra Senora del Rosario, 2020)
Introduction: Among malocclusions, that of cross-bite is the most prevalent among preschool children and is considered to be the main depreciator of the stomatognathic system and is further linked to a high risk of developing irreversible musculoskeletal sequelae in adulthood. Thus, it is important to choose an effective treatment early on that does not require the direct cooperation of the patient and that utilizes simple orthodontic techniques in its execution. The objective of this study was to report the efficacy of the Neuroclusal Rehabilitation (rno) treatment, with the Planas Direct Tracks technique in a case of early treatment of posterior crossbite, and the follow up of its occlusal stability for seven years. Case presentation: a 4-year-old female patient, who was bottle-fed, was diagnosed with a left unilateral functional posterior crossbite and midline deviation. For treatment of rno, occlusal adjustments were made on the teeth 63, 64 and 65 and after neuromuscular deprogramming, the Direct Planks were made in the crossed teeth. After 29 days, the bite was corrected, and occlusal adjustments were made in order to provide greater occlusal harmony. Monitoring and evaluation took place every six months for seven years in order to verify the balance and stability of the treatment. Conclusion: the rno treatment with the use of Planas Direct Tracks is an effective solution for the correction of posterior crossbite using a simple, low-cost technique that can be performed by general practitioners.
Intervención temprana de la mordida cruzada por la pista directa de planas: Relato de siete años de seguimiento
Intervenção precoce da mordida cruzada pela pistas diretas de planas: Relato de sete anos de seguimento
Keywords: Malocclusion; Occlusal adjustment; Preventive orthodontics